Beautiful victims: How the halo of attractiveness impacts judgments of celebrity and lay victims of online abuse. (May 2022) - Hand, Christopher J.; Scott, Graham G.
Abstract: Research has shown that celebrity and lay victims are attributed blame for cyberabuse incidents. The nature of victim-generated content and abuse volume contribute to victim blame (VB) and perceived severity (PS) of incidents. Complementary cyberbullying research demonstrates that perceived attractiveness co-varies with VB, suggesting a protective 'halo' related to the 'what is beautiful is good' phenomenon. To explore the inter-relationships between victim status (celebrity, lay-user), victim identity claims (initial tweets: negative, neutral, positive), and behavioral residue (abuse volume: low, high), we used a mixed-factors design; victim status was a between-groups factor, whereas initial tweet valence and abuse volume were within-participants factors. We measured perceptions of victim attractiveness, VB, and PS; additionally, we measured participants' ( N = 309) Dark Triad traits. In general, we found that celebrities received less blame than lay-users, and abuse against celebrities was perceived as more-severe. An exception was when celebrities initially tweeted negative content, in which case they received more blame. VB was influenced by social attractiveness, victim status, and initial tweet valence. PS was determined by abuse volume, task attractiveness, and initial tweet valence. Celebrities appear to be held in higher regard and considered more attractive than other social media users, affording them protection when abused online. Highlights: Celebrities targets were victim-blamed to a lesser extent than layperson targets following cyberabuse. Abusive incidents involving celebrity targets were perceived as more-severe than incidents involving laypersons. Celebrities are seen as more socially-, physically, and task-attractive than laypersons. Observer Psychopathy and Machiavellianism predict victim-blaming and perceptions of severity. Victim attractiveness and status predict victim-blaming and perceptions of severity.